Optimizing Site Planning and Testing of Wireless Lan Network (Al-Mansour Journal, 2023)
In Wireless Local Area Networks (WLAN) deployment, there are several criterions that should be addressed prior to any in-depth planning and implementation. The capacity, the coverage area and the network performance are impacted by several interacting factors that must be considered to meet the requirements of high availability, high performance, and mission critical environment.This paper discusses how practically optimizing WLAN networks based on methodologies stages for planning, designing, implementing, operating and then using modern techniques for testing WLAN to reach an optimized performance and services of a variety of wireless networks for indoor and outdoor applications by providing appropriate coverage and data throughput to all end users while keeping interference to minimum to insure the successful and efficient deployment of wireless local area networks